2013
DOI: 10.4317/medoral.18335
|View full text |Cite
|
Sign up to set email alerts
|

Canting of the occlusal plane: Perceptions of dental professionals and laypersons

Abstract: Objectives: To determine if canting of the occlusal plane influences esthetic evaluation of the smile among orthodontists, dentists and laypersons. Study Design: A frontal photo of a smile with 0º occlusal plane canting in relation to the bipupillary plane was modified using Adobe Photoshop C3 (Adobe Systems Inc, San José, California) to generate two images with occlusal plane inclinations of 2º and 4º. The three images were evaluated esthetically by orthodontists (n=40) general dentists (n=40) and laypersons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 21 publications
3
24
0
8
Order By: Relevance
“…Some studies compared directly dentists vs laypersons, finding tolerances of 1 mm for dentists and 3 mm for laypersons, 19 others found similarities between both groups. 20,21 The present study found the threshold at 2 (or the equivalent of 1 mm 19 ), corroborating the results of Padwa et al, 22 showing a slightly higher sensitivity of the laypersons interviewed compared to the literature. It is evident that there is a high variability of results in the literature regarding was to see if the nose and chin inclinations affected the ratings considering which side of the cant was involved.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Some studies compared directly dentists vs laypersons, finding tolerances of 1 mm for dentists and 3 mm for laypersons, 19 others found similarities between both groups. 20,21 The present study found the threshold at 2 (or the equivalent of 1 mm 19 ), corroborating the results of Padwa et al, 22 showing a slightly higher sensitivity of the laypersons interviewed compared to the literature. It is evident that there is a high variability of results in the literature regarding was to see if the nose and chin inclinations affected the ratings considering which side of the cant was involved.…”
Section: Discussionsupporting
confidence: 91%
“…Some studies compared directly dentists vs laypersons, finding tolerances of 1 mm for dentists and 3 mm for laypersons, others found similarities between both groups . The present study found the threshold at 2° (or the equivalent of 1 mm), corroborating the results of Padwa et al, showing a slightly higher sensitivity of the laypersons interviewed compared to the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Buccal corridor was difficult to be perceived even by dental specialist . Even more, 4 ° occlusal plane cant was considered normal by general dentists . Padwa et al reported that the perception of occlusal plane canting depends on the degree of inclination rather than the levels of experience of the observers.…”
Section: Discussionmentioning
confidence: 99%
“…Pour cette raison, les praticiens consid erent qu'une simple restauration du bord incisif serait plus simple à r ealiser qu'une modification du contour gingival. Among professional respondents, prosthodontists are most critical, followed by orthodontists, as shown by by Olivares et al [20]. N eanmoins, il est evident que dans une evaluation individuelle des images modifi ees celles qui ont et e jug ees esth etiques par tous les r epondants etaient celles montrant le bord incisif asym etrique de l'incisive centrale sup erieure, plus courte de 0,5 mm (n o 4) et la migration gingivale asym etrique de 2 mm de l'incisive centrale sup erieure (n o 8).…”
Section: Discussionunclassified
“…Janson et al [16], cependant, dans une revue syst ematique, ont conclu qu'une d erive de la ligne m ediane maxillaire jusqu'à 2,2 mm est esth etiquement acceptable pour les orthodontistes comme pour les non-professionnels. Parmi les r epondants professionnels, les dentistes proth esistes etaient les evaluateurs les plus critiques, suivis des orthodontistes, en concordance avec l' etude d'Olivares et al [20]. Cette disparit e au niveau des evaluations esth etiques est peutêtre due aux diff erences de mat eriel et de m ethode utilis es dans leurs etudes.…”
Section: Discussionunclassified